Body Image Satisfaction and its Relationship to the Reasons Why Young Women are Undergoing Cosmetic Surgery from their Perspectives - Joudeh, Nadia Fahad; Banat, Suhaila Mahmood (Journal of Educational and Psychological Sciences, 2020)
This study aimed to reveal the level of satisfaction of the body image and its relationship to the reasons why young women are undergoing cosmetic surgery from their perspectives. The sample of the study consisted of (150) young women who visit private beauty clinic. Two scales were developed: a scale of the level of satisfaction of body image consisting of (34) item and a scale of the reasons of why young women are undergoing cosmetic surgery consisting of (39) item. After insured the scales’ validity and reliability, the descriptive-correlational approach was used. The results of the study showed that the level of body image was moderate, and for the reasons of why young women are undergoing cosmetic surgery; the psychological dimension came in the first rank, While the vocational dimension came in the last rank. The results also found a positive correlation between body image satisfaction and the reasons why young women are undergoing cosmetic surgery. The results did not show differences in the level of satisfaction of the body image to the variable of marital status and economic level. While the results showed dissatisfaction with the body image due to age in favor of the category (31-40) and the educational qualification in favor of a diploma degree and below. As for the reasons for the young women undergoing cosmetic surgery, it was found that there were no statistically significant differences in the marital status and educational qualification variables, also, there were differences due to age only on the social dimension and in favor of (31 - 40), and there were differences attributed to the economic level in the social dimension in favor of the category (500-1000). Considering the results, the researcher recommended reinforcing the body image through nurture and guidance to raise the level of satisfaction with body image and to conduct more surveys, qualitative, and experimental studies related to cosmetic surgery other than the target category in this study, and for both sexes.